Longitudinal Utilization of Invasive Pain Treatment Procedures Among Veterans with Chronic Pain Following Use of Whole Health Services and Complementary and Integrative Health Therapies - Zeliadt SB; DeFaccio R; Carey EP; Etingen B; Rosser EW; Suri P; Chen JA; Bokhour BG; Coggeshall S (Journal of Pain Research, 2025)
Steven B Zeliadt,1,2 Rian DeFaccio,1 Evan P Carey,3 Bella Etingen,4,5 Ethan W Rosser,1 Pradeep Suri,6 Jessica A Chen,1 Barbara G Bokhour,7,8 Scott Coggeshall1 1VA Center of Innovation (COIN) for Veteran-Centered and Value-Driven Care, VA Puget Sound Healthcare System, Seattle, WA, USA; 2Department of Health Systems and Population Health, School of Public Health, University of Washington, Seattle, WA, USA; 3VA Center of Innovation (COIN) for Veteran-Centered and Value-Driven Care, Eastern Colorado Healthcare System, Denver, CO, USA; 4Research and Development Service, Dallas VA Medical Center, Dallas, TX, USA; 5Department of Public Health, Peter O’Donnell Jr. School of Public Health, UT Southwestern Medical Center, Dallas, TX, USA; 6Seattle Epidemiologic Research and Information Center (ERIC), VA Puget Sound Healthcare System, Seattle, WA, USA; 7Center for Healthcare Organization and Implementation Research, VA Bedford Healthcare System, Bedford, MA, USA; 8Department of Population and Quantitative Health Sciences, University of Massachusetts Chan Medical School, Worcester, MA, USACorrespondence: Steven B Zeliadt, VA Center of Innovation (COIN) for Veteran-Centered and Value-Driven Care, VA Puget Sound Healthcare System, 1660 South Columbian Way, S-15, Seattle, WA, 98108, USA, Tel +1 206 277-4175, Fax +1 206 764-2935, Email steven.zeliadt@va.govObjective: To assess whether Whole Health, a system of care that emphasizes non-pharmacological approaches for chronic pain management, is associated with changes in downstream utilization of invasive pain treatment procedures.Methods: Longitudinal retrospective cohort analysis of VHA administrative data. A total of 53,412 Veterans with chronic pain were identified between April and September 2018, with 584 initiating Whole Health and 3794 initiating a complementary and integrative health (CIH) therapy independent of Whole Health (CIH-only). Whole Health included use of coaching, personal health planning, and other services including CIH referral. CIH therapies included chiropractic care, acupuncture, massage therapy, yoga, Tai Chi/Qigong, and meditation. Propensity score matching was used to estimate expected rates of invasive pain treatment procedures 0– 3, 4– 12, and 13– 18 months after initiating Whole Health or CIH-only compared to similar Veterans who had not engaged in either.Results: Overall, 14% of the population were female, 11% had received prior spine injections, 3.3% had received surgery, and 0.4% had an implantable spinal stimulator. Whole Health use was associated with 42% (− 61% to − 17%) lower utilization of invasive pain procedures at three months compared to matched patients who did not use Whole Health. This reduction was attenuated at 18 months: 22% (− 39% to − 5%). CIH-only was associated with 18% (− 29% to − 4%) lower utilization at three months compared with matched patients, but differences were minimal at 18 months: 1% (− 9% to 9%).Discussion: Whole Health care, including CIH therapies, may help patients interrupt patterns of escalating and invasive pain care.Keywords: chronic pain, complementary and integrative health, invasive spine procedures, whole health, veterans